2016
DOI: 10.1103/physrevb.93.155152
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structure of palladium in the presence of many-body effects

Abstract: Including on-site electronic interactions described by the multi-orbital Hubbard model we study the correlation effects in the electronic structure of bulk palladium. We use a combined density functional and dynamical mean field theory, LDA+DMFT, based on the fluctuation exchange approximation. The agreement between the experimentally determined and the theoretical lattice constant and bulk modulus is improved when correlation effects are included. It is found that correlations modify the Fermi surface around … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 83 publications
4
22
0
Order By: Relevance
“…The flat band has a significant density of states (DOS) from the Pd d-orbitals of the 2D kagome lattice, whose energy is located right below the top valence bands. The Pd-dominant flat band over the whole reciprocal space remains to be robust for the accepted U value of ~ 1.5 eV for Pd atoms, which is a reasonable value according to previous studies 49 . As a further check of the validity of our calculated band structures, we were also able to extract the magnetic susceptibility using the obtained electronic band structures [50][51][52] .…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…The flat band has a significant density of states (DOS) from the Pd d-orbitals of the 2D kagome lattice, whose energy is located right below the top valence bands. The Pd-dominant flat band over the whole reciprocal space remains to be robust for the accepted U value of ~ 1.5 eV for Pd atoms, which is a reasonable value according to previous studies 49 . As a further check of the validity of our calculated band structures, we were also able to extract the magnetic susceptibility using the obtained electronic band structures [50][51][52] .…”
Section: Resultssupporting
confidence: 83%
“…The Pddominant flat band over the whole reciprocal space remains to be robust for the accepted U value of ~1.5 eV for Pd atoms, which is a reasonable value according to previous studies. 49 As a further check of the validity of our calculated band structures, we were also able to extract the magnetic susceptibility using the obtained electronic band structures [50][51][52] . The calculated diamagnetic susceptibilities are χ ⊥ = 2.38 × 10 -4 and χ ∥ = 2.00 × 10 -4 emu/mol, respectively, when the field is perpendicular and parallel to the ab plane.…”
Section: Resultsmentioning
confidence: 99%
“…More recently, a LDA+DMFT study 17 using a quantum Monte Carlo impurity solver found comparable electronic effective mass as in Ref. 13. In addition in Ref.…”
Section: Introductionmentioning
confidence: 56%
“…This is also true in the case of palladium for which the LDA calculation of the bulk modulus turns out to overestimate the experimental value by more than 10%. Indeed, using LDA+DMFT and employing a fluctuation exchange (FLEX) approximation as impurity solver in the Matsubara domain at T = 400 K, with a local Coulomb interaction U = 1 eV, and a local Hund's rule coupling J = 0.3 eV it was shown 13 that the experimental volume V = 99.3 a.u. 3 is reproduced and the deviation in the bulk modulus from the experimental value is significantly reduced (< 1 %).…”
Section: Introductionmentioning
confidence: 99%
“…During the 1970s, several theoretical and experimental studies focused on the electronic structure of Pd to determine the main features of the Fermi surface. Even today, it continues to attract the interest of scientists to explain subtler details such as the impact of electron-electron interactions [39] or the exact shape of the L-hole Fermi surface pocket [40] (see Fig. 1).…”
Section: Introductionmentioning
confidence: 99%